Management of erectile dysfunction after prostate cancer treatment: cross-sectional surveys of the perceptions and experiences of patients and healthcare professionals in the UK - Amy Dyer; Mike Kirby; Isabel D White; Alison Michelle Cooper (BMJ Open)
Objectives Erectile dysfunction (ED) is known to be a common consequence of radical treatment for prostate cancer (PCa) but is often under-reported and undertreated. This study aimed to explore how ED in patients with PCa is managed in real-life clinical practice, from the perspective of patients and healthcare professionals (HCPs).Design and setting This is a UK-wide cross-sectional survey of men with ED after treatment for PCa which covered assessment and discussion of erectile function, provision of supportive care and satisfaction with management. Parallel surveys of primary and secondary HCPs were also conducted.Results Responses were received from 546 men with ED after PCa treatment, 167 primary (general practitioners and practice nurses) and 94 secondary care HCPs (urologists and urology clinical nurse specialists). Survey findings revealed inadequate management of ED in primary care, particularly underprescribing of effective management options. A fifth of men (21%) were not offered any ED management, and a similar proportion (23%) were not satisfied with the way HCPs addressed their ED concerns. There was poor communication between HCPs and men, including failure to initiate discussions about ED and/or involve partners, with 12% of men not told that ED was a risk factor of PCa treatment. These issues seemed to reflect poor access to effective ED management or services and lack of primary HCP confidence in managing ED, as well as confusion over the roles and responsibilities among both HCPs and men.Conclusions This study confirms the need for better support for men from HCPs and more tailored and timely access to effective ED management after treatment for PCa. A clearly defined pathway is required for the discussion and management of ED, starting from the planning stage of PCa treatment. Improved adherence to ED management guidelines and better education and training for primary care HCPs are areas of priority.